Validation of non-classical homogeneous nucleation model for G-glass and L-glass formations in liquid elements with recent molecular dynamics simulations. (1st July 2021) - Tournier, Robert F.
Abstract: A first-order transition from liquid to homogenous glass denoted L -glass is predicted since 2016, in liquid elements having a Lindemann constant equal to 0.103, with a non-classical homogeneous nucleation model, accompanied by a latent heat of 10.5 % of the melting heat. The transition under pressure of 4 He is the first example of this phenomenon. Recent molecular dynamic simulations of Qi An et al identify, in addition, a first-order freezing transition from liquid (L) to metastable heterogenous solid-like phase, denoted as the G-glass, when a supercooled liquid evolves isothermally below its melting temperature Tm at deep undercooling. These observations are related to the general phenomenon of first-order transitions of glacial phases obtained by annealing above Tg at various heating or cooling rates or by isotherm annealing. The non-classical model of homogenous nucleation describes the first-order transitions of L-glass and G-glass to liquid in perfect agreement with these simulations. Graphical abstract: Image, graphical abstract